53 Effects Of GLP-1 eluting stem cell therapy on collagen remodelling in a porcine model of myocardial infarction. Issue 20 (23rd September 2011) - Wright, E J; Farrell, K A; Malik, N; Wallrapp, C; Geigle, P; Lewis, A L; Stratford, P W; Holt, C M
Abstract : Glucagon-like peptide-1 (GLP-1) is an incretin hormone with cardioprotective effects. Human stem cells (hMSCs) secreting a GLP-1 fusion protein and encapsulated in alginate (GLP-1 CellBeads) have been developed as a novel therapeutic. This study investigated the effects of GLP-1 CellBeads on post-MI healing in a porcine model. GLP-1 CellBeads were delivered to coronary artery branches, creating micro-infarcts and mild LV dysfunction. Cell-free beads (empty) and CellBeads containing hMSCs but not secreting GLP-1 (hMSC-beads) were delivered as controls. Left ventricular (LV) function, infarct size, myocyte cross-sectional area, total collagen content (picrosirius red staining) and collagen -1 and -3 levels (qRT-PCR) were analysed to determine therapeutic potential. Four weeks post-MI, only GLP-1 CellBead treatment produced significantly improved LV function compared to 30 min post-MI (44.00%±1.29% vs 49.75%±1.03%, p<0.001). This was also associated with less infarct (3.21%±0.90%) compared to control groups (empty; 17.70%±4.69% vs hMSC-beads: 16.71%±1.60%, p<0.05). Total collagen content (infarct) was increased following delivery of hMSC-beads and GLP-1 CellBeads compared to empty beads (6.87%±2.92% vs 19.63%±1.37% vs 16.88%±6.61%, p<0.05), with increases in collagen 1 and 3 mRNA synthesis observed in all groups. Border zone myocytes were significantly larger in all groups compared to control (non-infarcted) tissue (empty: 378.4±31.3; hMSC-beads: 364.6±15.7; GLP-1 CellBeads: 344.7±38.9; control: 132.7±13.0), with no differences in remote regions. Delivery of GLP-1 CellBeads restored LV function, limited infarct size, enhanced collagen scar formation, altered collagen mRNA synthesis and decreased border myocyte size. Effects observed were due to a combination of GLP-1 and paracrine factors released from the hMSCs.